2015
DOI: 10.1186/s13643-015-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and suicidal behaviors: a systematic review protocol

Abstract: BackgroundSuicide is among the leading causes of death worldwide. Suicide attempts and suicidal ideation are more common than completed suicide and are associated with psychological distress. These behaviors are considered risk factors of completed suicide. Considering the psychosocial stigma and medical comorbidities associated with obesity, an accumulating body of studies have investigated body mass index (BMI) as a potential risk factor of suicide. However, several cohort studies have demonstrated an invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 63 publications
1
22
1
2
Order By: Relevance
“…Excess body mass is a known risk factor for chronic illnesses, but the association between BMI and suicidal behavior has not yet been clarified (Perera et al, 2015). Excess body mass is a known risk factor for chronic illnesses, but the association between BMI and suicidal behavior has not yet been clarified (Perera et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Excess body mass is a known risk factor for chronic illnesses, but the association between BMI and suicidal behavior has not yet been clarified (Perera et al, 2015). Excess body mass is a known risk factor for chronic illnesses, but the association between BMI and suicidal behavior has not yet been clarified (Perera et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The methods of this systematic review were published in an a priori designed protocol (Perera et al., ) that was registered with PROSPERO. We provide a summary of the methods below.…”
Section: Methodsmentioning
confidence: 99%
“…No language restrictions were applied. A medical librarian (NB) assisted with the development of the search strategy (see Table of the published protocol; Perera et al., ). We also hand‐searched the reference lists of included articles and past reviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have revealed a consistent, longitudinal, and positive association between obesity and symptoms of depression (Mather et al 2009;Luppino et al 2010;Faith et al 2011). However, focusing on the complex link between obesity and suicidality, Klinitzke et al (2012) and Perera (2015) independently demonstrated in systematic overviews, that the current literature supports a significant inverse relationship between obesity and suicide. Therefore, the current progress in the field of bariatric surgery and its impact on self-harm behavior and suicidality is of growing relevance.…”
Section: Self-harm and Suicidalitymentioning
confidence: 99%